A CLINICAL OBSERVATIONAL STUDY TO EVALUATE THE COMBINED EFFECT OF DADRUGHNA LEPA AND PITTAKUSTAHARA KASHAYA IN MANAGEMENT OF DADRU (TINEA) - Ashwini S G; Waheeda Banu (International Journal of Ayurveda and Pharma Research, 2020)
Dadru is one among the Kushta described in the classical text books of Ayurveda which bears greater resemblance with Tinea or Ringworm Infection. It is the commonest single fungus group of infectious skin disorders found in unhygienic conditions of tropical and subtropical countries and most encountered in clinical practice. Unless properly treated they become chronic. Dadru is a disease where all the treatment modalities can be applied as per the requirement of the disease condition. Here in this study, patients diagnosed with Dadru were treated with Dadrughna Lepa externally and Pittaja Kustahara Kashaya internally for a period of 30 days and observations were recorded. Methods: 50 patients fulfilling the diagnostic and inclusion criteria were considered for this single group study of 30 days for each patient. Periodical assessment done during the course of treatment and observations recorded as per case proforma. The data collected during study were Statistical analysed and resultant overall effect of therapy is noted. Results: As a result, Out of 50 patients, highly significant results (p< 0.05) were obtained with respect to Kandu (Itching) (i.e. 75.61%), Raga (Redness)(79.61%), Daha (Burning sensation)(83.12%), Pidaka (Eruption) (84.21%), Rookshata (Dryness)(53.66%), Udgata Mandala (elevated lesion) (71.43%), Size and No. of Lesions (67.82%). Discussion: Out of 50 patients, 2 patients (4%) were getting No improvement, 4 patients (8%) observed to have Mild improvement, 16 patients (32%) were observed with Moderate improvement and 28 patients (56%) with Marked Improvement. Overall effect of the treatment observed is 75.25%.